2015
DOI: 10.1016/j.fertnstert.2015.03.037
|View full text |Cite
|
Sign up to set email alerts
|

PON1 polymorphisms are associated with polycystic ovary syndrome susceptibility, related traits, and PON1 activity in Indian women with the syndrome

Abstract: Our study showed that L55M, but not Q192R, polymorphism is significantly associated with reduced PCOS susceptibility only in lean women and also impacts glucose metabolism, lipid parameters, and hyperandrogenemia in them. Our study therefore suggests the possibility of differential genetic pathophysiology of PCOS between lean and obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
(70 reference statements)
2
14
0
Order By: Relevance
“…To our best knowledge, this is the first systematic review and meta-analysis of studies showing the potential Subtotal (I-squared = 0.0%, p = 0.848) Skrgatic L et al, 2012Joshi B et al, 2016Houjeghani S 2012Lauritsen MP et al, 2014Liu Q et al, 2008Song DK et al, 2014Meriem G et al, 2016Dikmen E et al, 2011 Subtotal (I-squared = 93.6%, p = 0.000) Pangaribuan B et al, 2012Baldani DP et al, 2015Schweighofer N et al, 2012Zhu Q et al, 2016 Case-control Study Anttila L et al, 1996Bendlov B et al, 2007Zhang Y et al, 2006ID Jamil AS et al, 2015 Cohort Study Koiou E et al, 2011Jayagopal et al, 2003Tarkun I et al, 2004El-Shal AS et al, 2013Abu HTM et al, 2016Alili A et al, 2014Chae SJ et al, 2010Prelevit GM et al, 1993 Subtotal (I-squared = 94.8%, p = 0.000) Ferk P et al, 2006Seiminska L et al, 2004Legro RS et al, 2002Tarkun S et al, 2010Atamer A et al, 2008Dadachanji R et al, 2015N. Xita et al, 2008Schüring AN et al, 2012Yasmin E et al, 2012 Cross-sectional Kim JW et al, 2012Kandasamy S et al, 2016Garcia MA et al, 2012Oh JY et al, 2009 -0.83 (-1.01, -0.64) endocrine abnormalities has been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, this is the first systematic review and meta-analysis of studies showing the potential Subtotal (I-squared = 0.0%, p = 0.848) Skrgatic L et al, 2012Joshi B et al, 2016Houjeghani S 2012Lauritsen MP et al, 2014Liu Q et al, 2008Song DK et al, 2014Meriem G et al, 2016Dikmen E et al, 2011 Subtotal (I-squared = 93.6%, p = 0.000) Pangaribuan B et al, 2012Baldani DP et al, 2015Schweighofer N et al, 2012Zhu Q et al, 2016 Case-control Study Anttila L et al, 1996Bendlov B et al, 2007Zhang Y et al, 2006ID Jamil AS et al, 2015 Cohort Study Koiou E et al, 2011Jayagopal et al, 2003Tarkun I et al, 2004El-Shal AS et al, 2013Abu HTM et al, 2016Alili A et al, 2014Chae SJ et al, 2010Prelevit GM et al, 1993 Subtotal (I-squared = 94.8%, p = 0.000) Ferk P et al, 2006Seiminska L et al, 2004Legro RS et al, 2002Tarkun S et al, 2010Atamer A et al, 2008Dadachanji R et al, 2015N. Xita et al, 2008Schüring AN et al, 2012Yasmin E et al, 2012 Cross-sectional Kim JW et al, 2012Kandasamy S et al, 2016Garcia MA et al, 2012Oh JY et al, 2009 -0.83 (-1.01, -0.64) endocrine abnormalities has been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 39 observational cross sectional, prospective cohort, and case control studies involving 5,121 patients and 5,059 controls were included. Of all the studies, 18 were performed in Europe [Dadachanji et al 2015;Lauritsen et al 2014;Schweighofer et al 2012;Kim et al 2012;Pangaribuan et al 2012;Schüring et al 2012;Houjeghani et al 2012;Koiou et al 2011;Tarkun et al 2004;Liu et al 2008;Li et al 2006;Sieminska et al 2004;Richard 2002;Lin et al 2015;Jayagopal 2003;Elci et al 2016;Kim et al 2013;Danilowicz et al 2014], 18 in Asia [Zhu et al 2016;Jamil et al 2015;Baldani et al 2015;O'Reilly et al 2014;Martínez-García et al 2012;Alili and Idrizi 2014;El-Shal et al 2013;Skrgatic et al 2012;Dikmen 2011;Chae et al 2010;Oh et al 2009;Xita et al 2008;Bendlov et al 2007;Atamer et al 2008;Ferk et al 2007, Tarkun et al 2010Anttila et al 1996;Prelević 1993], 2 in Africa [Song et al 2014;Yasmin et al 2013], and 1 in North America [Kim et al 2014]. Studies used a variety of methods to identify patients with PCOS.…”
Section: Characteristics and Quality Assessment Of The Studies For Sementioning
confidence: 99%
“…Two polymorphisms (L55M and Q192R) of paraoxonase 1 ( PON1 ) gene were studied for their association with PCOS susceptibility and related traits in Indian women from Mumbai63, and the authors found that one of those SNPs (L55M) was associated with reduced PCOS susceptibility only in lean women and that it also impacted features such as hyperandrogenemia, lipid parameters and glucose metabolism in these women. This led the authors to suggest that the genetic pathophysiology of PCOS was different in lean and obese women.…”
Section: Studies In the Genetics Of Pcos From Indiamentioning
confidence: 99%
“…Moreover, the impact of gene-environment and epigenetic alterations in addition to sequence variations may not be suitably captured (31). Previous studies have evidenced that genetic dissimilarities exist when the study groups were classified based on obesity (42,105,(118)(119)(120)or different diagnostic criteria were used for classifying PCOS(121).…”
Section: Discussionmentioning
confidence: 99%